Studi Persepsi Hubungan Non-Conforming Fashion Behavior dengan Tingkat Kreativitas Terhadap Masyarakat di Kota Malang - Bintang Pramudya PP (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Howard in his book entitled Human Visual Orientation explains that humans are visual creatures, humans also often associate certain visual things with certain meanings, for example when the sky is cloudy it will mean that soon it will rain, humans also connote colors to different personalities. This also applies to the use of certain clothing, where certain types of clothing are able to give rise to perceptions in the human mind, in this case focusing on the perception of the level of creativity of an individual when wearing certain attire. The following research is important to confirm the perception of the people in Malang about the clothes worn, in the collection can be done by random sampling, where 220 speakers were randomly selected to order the clothes that have been selected from the most creative to the least creative ones. From the results of the analysis, it can be processed into a diagram for later analysis. The results obtained show that the use of informal clothing (non-conforming behavior) gives the impression of being unprofessional in the community.